General Elections 15 Oct 2019 Final Report - Hanlon, Joseph; Cortez, Edson; Nhancale, Sheila; Mendonça, Magda; Bande, Aldemiro; Nhacume, Nelia; Mahiquene, Telma (Mozambique Political Process Bulletin 58, 2020)
Frelimo and President Filipe Nyusi swept away the opposition in the 15 October 2019 general elections, matching Armando Guebuza's 2009 landslide. But there were widespead reports of misconduct. On a 52% turnout, Nyusi won 73% of the vote with over 50% in all provinces. Frelimo won majorities in all provincial parliaments and in the first ever election of governors, Frelimo won all ten.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; demographics / demografia; electoral geography / geografia eleitoral

Geografia Eleitoral e Insurgência em Cabo Delgado - Brito, Luís de (Desafios para Moçambique, 2020)
This chapter looks at the origins of the extremist insurgency in Cabo Delgado and posists that to understand its origins, we must look beyond religious extremeism and to other factors in order to analyse the situation from difference perspectives. This study looked at electoral data in Cabo Delgado to determine if there is a relationship bwtween voting patterns, including abstention, and political cleavages and social conflict.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; Northern PEA; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; electoral geography / geografia eleitoral

Republic of Mozambique: Final Report General and Provincial Assembly Elections - European Union Election Observation Missionn (European Union Election Observation Mission, 2019)
On 15 October, Mozambicans elected the president, members of the Assembly of the Republic, members of the 10 provincial assemblies, and 10 provincial governors. Although there was a considerable number of participants, including recently registered political parties, the electoral process was dominated by the three main parties: the ruling Mozambican Liberation Front (FRELIMO), the main opposition Mozambican National Resistance (RENAMO), and the Mozambican Democratic Movement (MDM)
Keywords: G - Mozambique / Moçambique; L - english / inglês; electoral geography / geografia eleitoral

Elite Bargains and Political Deals Project: Mozambique Case Study - Vines, Alex (UK Government Stabilisation Unit, 2018)
This case study is one of a series commissioned to support the Stabilisation Unit’s (SU) development of an evidence base relating to elite bargains and political deals. The project explores how national and international interventions have and have not been effective in fostering and sustaining political deals and elite bargains; and whether or not these political deals and elite bargains have helped reduce violence, increased local, regional and national stability and contributed to the strengthening of the relevant political settlement. Drawing on the case studies, the SU has developed a series of summary papers that bring together the project’s key findings and will underpin the revision of the existing ‘UK Approach to Stabilisation’ (2014) paper. The project also contributes to the SU’s growing engagement and expertise in this area and provides a comprehensive analytical resource for those inside and outside government
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; L - english / inglês; conflict - civil war / conflito - guerra civil; conflict / conflito; decentralization / descentralização; electoral geography / geografia eleitoral

Os Municípios dos “Outros”. Alternância do poder local em Moçambique? O caso de Angoche - Rosário, Domingos Manuel do (Cadernos de Estudos Africanos, 2015)
As eleições municipais de 2003 marcaram o início do exercício do poder local pela Renamo no município de Angoche. Quais são os factores explicativos desta situação eleitoral local? A partir de uma perspectiva sócio-histórica, este artigo procura compreender como é que a evolução política e administrativa destes territórios influenciou a lógica do poder local. São as relações estabelecidas entre as populações e o Estado e a forma como a municipalização foi desenhada e implementada desde 1994 pela Frelimo que não proporcionam condições favoráveis à criação de um pluralismo político, na medida em que o partido dominante consegue, através do controlo que exerce sobre o Estado central, instrumentalizar os recursos e fortificar suas bases políticas e eleitorais.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Angoche; L - portuguese / português; Northern PEA; electoral geography / geografia eleitoral

Campos de batalha da cidadania no Norte de Moçambique - Temudo, Marina Padrão (Cadernos de Estudos Africanos, 2005)
Durante muitos anos, a ideia de que a guerra civil que assolou Moçambique era conduzida por um exército mercenário ao serviço de interesses externos foi considerada inquestionável, desconhecendo-se que a Renamo possuía uma base social de apoio rural e que a produção agrícola constituía uma das fontes de financiamento da guerra. Após a independência, o partido-Estado Frelimo provocou uma desestruturação social, económica, política e cultural das sociedades rurais, conduzindo um projecto de desenvolvimento e de construção da nação autoritário e centralizado, que pôs em causa direitos fundamentais de cidadania. A adesão à guerra de parte da população pode assim ser interpretada como uma tentativa de conquista desses direitos. Neste trabalho, através de dois estudos de caso contrastantes, pretende-se revelar as estratégias de reprodução social e económica que permitiram a sobrevivência das populações durante o conflito e a posterior reconstrução, mas também as múltiplas formas que a afirmação dos direitos de cidadania pode encobrir.
Keywords: G - Mozambique / Moçambique; L - portuguese / português; conflict / conflito; electoral geography / geografia eleitoral